PENYUSUNAN TATA TERTIB DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN SITUBONDO PASCA FASILITASI GUBERNUR JAWA TIMUR - Heriyanto Heriyanto; Abd. Rahman (LP2M Universitas Ibrahimy, 2021)
Based on the results of the plenary Session of the Situbondo Regional People's Representative Council, it is necessary to revise the Situbondo Regional People's Representative Council Regulation Number 01 of 2018 concerning the order of the Situbondo Regional People's Representative Council Regulations. Therefore, a Draft Regulation is prepared to be facilitated by the East Java Governor. There are several important points that became notes for the post-facilitation facilitation of the Governor of East Java to be included in the material for the rules. The purpose of this service is to direct the preparation of regulations in accordance with the hierarchical rules of legislation. This outreach program used the juridical – normative method through the approach of legislation. The results of this outreach program are in the form of a draft regulation for the Situbondo Regional People's Representative Council.